ANALISIS PENGARUH KINERJA KEUANGAN DAN NILAI TUKAR TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR - Ashwa, Anya Peditha (Program Studi Ekonomi Pembangunan, 2023)
The purpose of this study is to analyze the effect of financial performance and exchange rates on stock prices in manufacturing companies listed on the Indonesia Stock Exchange in 2018-2021. The method used in this study is multiple linear regression analysis on panel data using the Eviews 9 analysis tool and using a quantitative approach sourced from IDX data used by 95 companies and 3 manufacturing industry sectors. The results of this study are based on the F test that the variables CR, ROE, DER, PER & exchange rates have a joint effect on stock prices. Whereas in the t test (partial) the variable Return on equity (ROE) affects stock prices. This shows that CR has a positive and insignificant effect on stock prices, ROE & DER have a significant positive effect on stock prices, then PER & Exchange rates have a negative and insignificant effect so that it will have a positive impact on manufacturing companies where these companies are able to reduce the impact caused by the depreciation of the Indonesian exchange rate.